Reported use of evidence in clinical practice: a survey of rehabilitation practices in Norway - Jennifer L. Moore; Svein Friis; Ian D. Graham; Elisabeth Troøyen Gundersen; Jan E. Nordvik (BMC, 2018)
Abstract Background The South Eastern Health Region in Norway serves approximately 2.8 million people, which is more than half of Norway's population. Physical medicine and rehabilitation services are provided by 9 public hospital trusts and 30 private rehabilitation facilities. The purposes of this study were to conduct a psychometric analysis of the EBP Implementation Scale (EBPIS) and describe rehabilitation clinicians' self-reported 1) use of evidence-based practices (EBPs), 2) use of EBPs across hospitals, and 3) determine factors associated with use of EBPs in the South Eastern Health Region in Norway. Methods A cross-sectional study using an online survey was conducted with public hospitals and private rehabilitation centers. The survey, which was distributed throughout the region, included the EBPIS, 8 questions related to EBP in the health region, and demographics. Response frequencies were calculated and described. Internal consistency and factor structure of the EBPIS and its subscales were determined. Associations and differences in groups with similar demographics, EBPIS scores, and use of EBPs were identified. Results A total of 316 individuals completed the survey, including allied health clinicians, nurses, psychologists, social workers, and physicians. The EBPIS mean score was 30/72. A factor analysis identified that the EBPIS can be divided into 3 subscales: literature search and critical appraisal (α = .80), knowledge sharing (α = .83), and practice evaluation (α = .74). EBP activities reported were primarily related to literature searches, critical appraisal, and discussing evidence. Approximately 65 and 75% of respondents agreed that the same OMs and evidence based interventions were used within the local clinic respectively. Fewer agreed that the same OMs (13%) and evidence-based interventions (39%) are used regionally. Conclusion The EBPIS and its subscales demonstrated excellent internal consistency. Practice variability exists in rehabilitation throughout Southeastern Norway. An increased emphasis on use of EBP throughout the region is needed.